Early life maltreatment but not lifetime depression predicts insecure attachment in women - Zietlow, Anna-Lena; Nonnenmacher, Nora; Herpertz, Sabine; Neukel, Corinne; Fuchs, Anna (Archives of women's mental health, 2017)
Early life maltreatment (ELM) poses a risk for the development of insecure attachment and depression over the life span, depending on the type of maltreatment (physical, sexual, emotional, neglect) and its severity. The aim of this study was to investigate the influence of ELM and lifetime depression on adult insecure attachment in a female sample (N = 188), consisting of n = 81 women with ELM and n = 107 without ELM. Women with ELM reported significantly higher scores on insecure attachment than women without ELM. A significant interaction effect for ELM × lifetime depression was found: Contradictory to the hypotheses, women with ELM but without lifetime depression scored highest on avoidant attachment, differing significantly from women with ELM and lifetime depression, even though the severity of ELM was higher among women with ELM and lifetime depression and they experienced significantly more severe neglect and sexual abuse, but not physical or emotional abuse. Regression analyses revealed that ELM was the only predictor of avoidant attachment, explaining 15.5% of the variance. Results underline the strong influence of ELM on adult attachment and are of special importance for prevention and intervention programs.